Time Control Chart for Two Inverted Models - Subba Rao, R; Pushpa Latha, M; R.L. Kantam, R (International Journal of Engineering and Technology, 2018)
Control charts are one of the powerful techniques of Statistical Process Control. Control charts are widely accepted and applied in industry which can be used to improve productivity, prevent defects and unnecessary process adjustment. Moreover, they also provide information in diagnosis and process capability. Life time data generally contain the failure times of sample products or inter failure times or number of failures experienced in a given time.Â The time to failure of a product is to be considered as a quality characteristic to assess the quality of the product.Â Control limits are evaluated for the time to failure.Â In this paper the time to failure of a product is considered to follow Inverse Rayleigh and Inverse Half Logistic distributions.Â Life time data are compared with the control limits to judge the quality performance of the product.Â Â